2016
DOI: 10.16920/jeet/2016/v0i0/85532
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Teaching and Learning for Basic Electrical Engineering Course Using Simulation as a Tool

Abstract: Abstract:One of the common difficulties faced by an entrant of an undergraduate course studying Electrical Engineering is in understanding the fundamentals of Alternating circuits (a.c.). In order to address the identified difficulty, modern engineering tool was introduced to enhance the learning in a.c. circuits as simulation tool plays an important role within the frame of teaching and learning in education across the world. With the performance of students in continuous internal examination (CIE) being less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Simulation environments help learners to understand the concepts better by extracting knowledge in the process of completion of a task. If the task is an assignment it will help the learners to discriminate between different variables, the hypotheses, and interpretation of the experimental results [18].The effectiveness of using modern engineering tool was presented to enhance the learning in fundamental course of electrical engineering as simulation tool plays an important role within the frame of teaching and learning in education across the world [25]. In control systems engineering, simulation is one of the important parameters for enhancing students' learning.…”
Section: Simulation As a Basic Tool For Learningmentioning
confidence: 99%
“…Simulation environments help learners to understand the concepts better by extracting knowledge in the process of completion of a task. If the task is an assignment it will help the learners to discriminate between different variables, the hypotheses, and interpretation of the experimental results [18].The effectiveness of using modern engineering tool was presented to enhance the learning in fundamental course of electrical engineering as simulation tool plays an important role within the frame of teaching and learning in education across the world [25]. In control systems engineering, simulation is one of the important parameters for enhancing students' learning.…”
Section: Simulation As a Basic Tool For Learningmentioning
confidence: 99%
“…The results of these showed that LT methods can increase student's achievement efficiently in challenging courses. Software simulation was used to enhance student's comprehension in Electric Circuit course by Itagi [5] and Salunke [6] and it has been successfully increased student's understanding in the class. Based on those references and our experiences in Electric Circuits teaching for about 14 years, a combination of LT method and software simulation will be suitable to be implemented in our class.…”
Section: Rudimentarymentioning
confidence: 99%